USATF/St. Vincent Sports Performance Elite Athlete Medical Support Program
In an effort to provide additional medical support to our elite athletes, USA Track Field has worked closely with St. Vincent Sports Performance to design an elite athlete health care program. This program which is presented here is designed to compliment other USATF and USOC insurance and medical support programs. St. Vincent is a nationally recognized hospital system and health network that has extensive experience serving professional athletes, including NFL and NBA players, Olympians and top race car drivers.